Persepsi Mahasiswa mengenai Pembelajaran melalui Tugas pada Pembelajaran Tatap Muka Terbatas - Paskalina Widiastuti Ratnaningsih (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study is aimed to find students’ perceptions on learning by giving assignment in limited face-to-face learning. In this pandemic time, teaching-learning activity is conducted limited and follows health protocol. One of the teaching-learning activities in the class is by giving assignment. Assignment in this teaching-learning activity is in the English teaching-learning activity context. By giving various kinds of assignments during teaching-learning activities, the researcher will explore more about students’ perceptions. The method used in this research is survey. The research result was the students more understood in doing the assignment when they attended the limited face-to-face learning. Students could also more be able to speak English and wrote in English well based on the assignment given.